Gugatan warga melalui citizen lawsuit pada kebakaran hutan dan lahan dalam konsep ekokarsi Tinjauan putusan MA no 3555 kpdt 2018 - Wisnu Sapto Nugroho; Romana Harjiyatni; Sunarya Rahardja (Kajian Hasil Penelitian Hukum, 2020)
The concept of ecocracy  in the legal system in Indonesia is contained in the constitution of the Republic of Indonesia, particularly in Undang-Undang Dasar Negara Republik Indonesia Tahun 1945. With this concept nature is protected, citizens obtain the right to the environment and sustainable development is realized. But in practice, the concept is not easy to realize because environmental problems in Indonesia are alarming. One concern related to the environment is forest and land fires that are difficult to control. The government as the organizer of the state, especially in the context of ensuring the protection, enforcement and fulfillment of the right to the environment, fails to realize that concept. The existence of a citizen lawsuit with a citizen lawsuit mechanism in the case of forest and land fires in Central Kalimantan is a form of concern, concern and demands of citizens so that their rights to the environment are guaranteed, protected and enforced. In this paper the authors analyze the Putusan MA Nomor 3555K PDT 2018. The purpose of this study was to determine the position of citizen lawsuit in legal arrangements in Indonesia, how to enforce environmental law, specifically handling forest fires in the presence of citizen claims through citizen lawsuit mechanisms and how to embody the concept of natural sovereignty ecocracy after citizen lawsuits through citizen lawsuit mechanisms from the issuance of Putusan MA Nomor 3555 K  PDT 2018. The method used in this study is research with socio legal methods. In accordance with that method, the authors conducted an analysis with legal hermeneutics. The author found the decision of the Putusan MA Nomor 3555 K PDT  2018 showing that the law is in favor of the environment, the acceptance of citizens' claims through a citizen lawsuit mechanism and efforts to uphold the concept of an ecocracy.